1993
DOI: 10.1002/j.1460-2075.1993.tb05750.x
|View full text |Cite
|
Sign up to set email alerts
|

The bluetail transposon: evidence for independent cis-regulatory domains and domain boundaries in the bithorax complex.

Abstract: An extremely large cis‐regulatory region generates the parasegment‐specific expression patterns of the homeotic genes in the bithorax complex. We present evidence supporting the idea that this cis‐regulatory region is subdivided into independent cis‐regulatory domains. We describe a Ubx‐lacZ transposon which is inserted into one of these domains, iab‐7. The PS12‐specific pattern of LacZ expression from this reporter indicates that it is subject to the control of the iab‐7 cis‐regulatory domain, but is protecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
156
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(167 citation statements)
references
References 60 publications
10
156
0
1
Order By: Relevance
“…If the initial activation of the cis-regulatory elements in the iab regions is dependent on the intergenic transcripts, then it would be necessary not only to have unique transcription patterns within each region but also to ensure that transcription does not spread from one region to the next. Our study provides evidence that the insulators that organize the different iab regions into discrete chromatin domains (8,14,15) act to regulate the intergenic transcription program in this way.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…If the initial activation of the cis-regulatory elements in the iab regions is dependent on the intergenic transcripts, then it would be necessary not only to have unique transcription patterns within each region but also to ensure that transcription does not spread from one region to the next. Our study provides evidence that the insulators that organize the different iab regions into discrete chromatin domains (8,14,15) act to regulate the intergenic transcription program in this way.…”
Section: Discussionmentioning
confidence: 68%
“…Genetic, transgenic, and molecular studies have identified a number of classes of distinct cis-regulatory elements within the iab regions capable of directing abdA and AbdB expression. Insulator DNAs have been identified at the boundaries of the iab8-iab7 domains (Frontabdominal-8, Fab8) (4), iab7-iab6 domains (Fab7) (5)(6)(7)(8)(9)(10), and iab5-iab4 domains (Miscadastral pigmentation, Mcp) ( Fig. 1 A) (7,11).…”
Section: E Xpression Of the Abdominal-a (Abda) And Abdominal-b (Abdb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Only insertions close to the promoter of a BXC gene report the entire expression pattern of this gene. [29][30][31][32] Regional reporting may not be restricted to the exceptional HOX gene clusters. In decapentaplegic (dpp), a hobo enhancer trap insertion into the "disc region" rendered predominantly the activity of this regulatory region.…”
Section: Resultsmentioning
confidence: 99%
“…But, with our current knowledge, it is not possible to say exactly why. For Drosophila Hox clusters the presence of boundary elements that make the function of cis-regulatory elements more modular could be a factor contributing to their structural flexibility (43,44). The nature of the differences, however, is obvious, with vertebrate Hox clusters being more constrained than invertebrate Hox clusters.…”
mentioning
confidence: 99%